DAERAH JELAJAH MASYARAKAT PENDUKUNG GUA HUNIAN DI KECAMATAN DANDER, KABUPATEN BOJONEGORO - Ulce Oktrivia (Naditira Widya, 2008)
Site catchment analysis in archaeology stresses on the examination of the relationship between human and its natural environment. This analysis performed based on the assumption that the benefiting of natural resource surrounds a settlement shows different distance from one to the other and that sites location will be in minimum distance to the resource. This article discuss a site catchment analysis employed to identify sites range and location of natural resource commonly exploited by cave dwellers in Dander, Bojonegoro.